'Personalized medicine': what's in a name?. (March 2014) - Pokorska-Bocci, Anna; Stewart, Alison; Sagoo, Gurdeep S; Hall, Alison; Kroese, Mark; Burton, Hilary
Over the last decade genomics and other molecular biosciences have enabled new capabilities that, according to many, have the potential to revolutionize medicine and healthcare. These developments have been associated with a range of terminologies, including 'precision', 'personalized', 'individualized' and 'stratified' medicine. In this article, based on a literature review, we examine how the terms have arisen and their various meanings and definitions. We discuss the impact of the new technologies on disease classification, prevention and management. We suggest that although genomics and molecular biosciences will undoubtedly greatly enhance the power of medicine, they will not lead to a conceptually new paradigm of medical care. What is new is the portfolio of modern tools that medicine and healthcare can use for better targeted approaches to health and disease management, and the sociopolitical contexts within which these tools are applied.